School quotidian and (dis)respect: what the school occurrence books say - Quevedo Goethel, Elisiane Spencer [UNESP]; Cardoso, Priscila Carla [UNESP]; Fonseca, Debora Cristina [UNESP] (Univ Federal Santa Maria, 2017)
This article aims to discuss how respect and disrespect appear in school quotidian and are signified in the speeches and in the registers of educators. For that, data collected in the School Occurrence Books (LOE) were analyzed. This is a documentary research of qualitative analysis, where the technique of content analysis was used. The discussion had as theoretical contribution the historical-cultural theory. The study points out the need to understand how the construction of respect by those who work in the school environment takes place, as well as its important role in this process, while taking into account issues such as culture, authority and commitment to guarantee access of knowledge.
Keywords: School's occurrence books/occurrence books; Respect; Disrespect; School quotidian